Infection on a chip: a microscale platform for simple and sensitive cell-based virus assays - Zhu, Ying (Springer US, 2009)
The plaque assay has long served as the “gold standard” to measure virus infectivity and test antiviral drugs, but the assay is labor-intensive, lacks sensitivity, uses excessive reagents, and is hard to automate. Recent modification of the assay to exploit flow-enhanced virus spread with quantitative imaging has increased its sensitivity. Here we performed flow-enhanced infection assays in microscale channels, employing passive fluid pumping to inoculate cell monolayers with virus and drive infection spread. Our test of an antiviral drug (5-fluorouracil) against vesicular stomatitis virus infections of BHK cell monolayers yielded a two-fold improvement in sensitivity, relative to the standard assay based on plaque counting. The reduction in scale, simplified fluid handling, image-based quantification, and higher assay sensitivity will enable infection measurements for high-throughput drug screening, sero-conversion testing, and patient-specific diagnosis of viral infections. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10544-008-9263-7) contains supplementary material, which is available to authorized users.